Education Based on Indigenous Ethics: The Aims of the Centre of Arts and Crafts for the First Peoples of Mexico - Morga, Alejandro Castillo (Concilium, 2019)
The present context needs the ideas of those who have been excluded throughout history to deal with the crisis humanity faces today. The crisis produced by modernity and the colonial system requires the voices of the other traditions to be more present in the public debate if we are to ensure the survival of the community of life on the planet. A critique of the system in terms of indigenous ethics seeks to present a vision of how the Amerindian nations take responsibility of the lives of their peoples through education, life communities integrated with a specific ecosystem, with a territory. The Arts and Crafts Centre initiative for the first peoples sets out to be a platform to promote education using the sensibility and knowledge of the peoples.